Review of applied mathematical models for describing the behaviour of aqueous humor in eye structures - Dzierka, Martyna; Jurczak, Paweł (Zielona Góra: Uniwersytet Zielonogórski)
In the paper, currently used methods for modeling the flow of the aqueous humor through eye structures are presented. Then a computational model based on rheological models of Newtonian and non-Newtonian fluids is proposed. The proposed model may be used for modeling the flow of the aqueous humor through the trabecular meshwork. The trabecular meshwork is modeled as an array of rectilinear parallel capillary tubes. The flow of Newtonian and non-Newtonian fluids is considered. As a results of discussion mathematical equations of permeability of porous media and velocity of fluid flow through porous media have been received.
Keywords: porous medium; Newtonian fluid; non-Newtonian fluid; coupe stress fluid; generalized second grade fluid; Darcy`s rule; aqueous humor flow; trabecular meshwork; intraocular pressure; glaucoma